An Overview of Monitoring Patient Safety in Nurses: A Comparative Analysis of Demographic Characteristics - Amira Sekar Amalia; Ekorini Listiowati; Sri Muliati Abdullah (Jurnal Pendidikan Indonesia, 2025)
Harmful events in the handling of patients in hospitals can be prevented by the principle of patient safety. Nurses as part of the health workforce have an important role in the implementation of patient safety, as well as nurses who become clinical educators who assist nursing students in carrying out studies in teaching hospitals. The success of achieving goals, the high quality of patient safety, is half determined by the plan that has been set and the other half functions by supervision or monitoring. This study aims to analyze the picture of monitoring patient safety in nurses. This research method uses a quantitative research with analytic observational methods and cross sectional approaches. In this study, it was found that the monitoring of patient safety by nurses to nursing students was well implemented and obtained a high implementation score. There are no differences in monitoring patient safety carried out by nurses between age groups, gender, last education, or length of work.